ANALYSIS OF SUSTAINABLE BUSINESS MODEL DEVELOPMENT IN MSMES WITH THE MAQASHID SHARIA APPROACH IN KUALUH HULU DISTRICT, NORTH LABUHANBATU REGENCY - Fitri Adinda Pasaribu; Sri Ramadani; Muhammad Ikhsan Harahap (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This study aims to analyze the development of sustainable business models in Micro, Small, and Medium Enterprises (MSMEs) in Kualuh Hulu District, North Labuhanbatu Regency, using the Maqashid Sharia approach. Maqashid Sharia, as a conceptual framework in Islamic law, focuses on five main goals: safeguarding religion, soul, intellect, heredity, and property. This research uses a qualitative method. The results of the study show that most MSMEs in Kualuh Hulu have not fully implemented sustainability principles in their business operations. The analysis further identifies several inhibiting and driving factors in the implementation of sustainable business models that are in accordance with Maqashid Sharia. Hindering factors include a lack of knowledge and resources, while driving factors include community support and positive market potential for halal and environmentally friendly products. This study suggests several strategies to develop sustainable business models for MSMEs based on Maqashid Sharia, such as capacity building through training and mentoring, strengthening sharia-oriented business networks, and developing products and services that meet sustainability and sharia standards. Thus, it is hoped that MSMEs in Kualuh Hulu District can increase competitiveness while contributing to sustainable economic development and in accordance with Islamic principles.